PENERAPAN BIAYA RELEVAN DALAM PENGAMBILAN KEPUTUSAN MEMBUAT SENDIRI ATAU MEMBELI â€œKALENGâ€ PADA PT. DEHO BITUNG - Rumopa, Inria; Ilat, Ventje; Elim, Inggriani (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
Every company both small companies and large corporations in carrying out its operations, basically focused on specific objectives. This study aims to determine the application of the relevant costs in the decision to make or buy an adjuvant that is canned. This research is a descriptive study with a quantitative approach. This research was conducted at PT. Deho Bitung as a research object which is located on Highway Madidir Bitung. Differential cost analysis is indispensable in accordance with the problems faced by companies in an effort to increase profits and reduce losses. Results seen from the comparison showed differential costs better decision taken by PT. Deho is purchased from outside the adjuvant cans because the costs were smaller or more efficient than making its own adjuvant cans.